DEVELOPMENT OF STEM-BASED ANIMATED VIDEO MEDIA FOR TEACHING SCIENCE MATERIAL ON THE CHARACTERISTICS OF LIVING THINGS - Fajar Eka Mardika; Arina Restian (JURNAL EDUSCIENCE, 2026)
Purpose - This research study aims to develop, test, and evaluate STEM animated science learning videos about the characteristics of living things for children in the lower elementary school. The purpose of this media is to convey scientific ideas and increase student participation through more meaningful, interactive presentations.Methodology – The research and development (R&D) approach to this study followed the ADDIE model. This was a small-scale study involving 15 third graders at SDN Mulyoagung 01 Dau, Malang Regency. The learning included guided viewing of STEM-based animated videos, small-group activities using STEM-related worksheets (LKPD), and individual assessment. Information was collected using professional validation tools, student response questionnaires, classroom observations, group worksheets, and individual evaluation outcomes, and measures were conducted in both descriptive and quantitative, as well as qualitative, ways.Findings – Based on assessments by subject matter and media experts, the STEM-based animated video has a very high level of feasibility (M = 84%). With a gain score of 0.84, limited trials show an increase in students' conceptual understanding. According to student responses, 86.7% found this media interesting, easy to understand, and helpful for visualizing the characteristics of living things. As a result, STEM-based animated videos have proven useful as an alternative for science instruction in lower grades.Contribution – This study contributes to the creation of digital learning resources that incorporate STEM methods in elementary school science education. It also offers a media development model to help teachers and researchers improve students' science literacy from an early stage of education.